2022
DOI: 10.1177/87551225221076327
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Perspectives on the Use of Telepharmacy in Response to COVID-19 Pandemic in Ho Chi Minh City, Vietnam

Abstract: Introduction: Telepharmacy, the application of information and communication technologies in healthcare services, has been adopted in many countries to provide patients with pharmaceutical care. However, it has yet to be widely used in Vietnam. This study was conducted to assess the current status of use and the factors associated with the willingness to use telepharmacy of pharmacists in Vietnam. Methods: A descriptive cross-sectional study was conducted from February to July 2021; 414 pharmacists were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Pharmacists and student pharmacists should understand the application of telecommunication technology in the pharmacy field to provide the best services. Worldwide there is evidence showing that the proportion of pharmacy student knowledge of tele-pharmacy was 60.3% in the United States [ 8 ], 42% in Riyadh city of Saudi Arabia [ 9 ], and 67% in Malaysia [ 4 ]. Whereas the proportion of perception towards tele-pharmacy was 87% in the University of Tennessee [ 8 ], 70.6% in Jordan [ 10 ], 61% in Malaysia [ 4 ], and 40% in Pakistan [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists and student pharmacists should understand the application of telecommunication technology in the pharmacy field to provide the best services. Worldwide there is evidence showing that the proportion of pharmacy student knowledge of tele-pharmacy was 60.3% in the United States [ 8 ], 42% in Riyadh city of Saudi Arabia [ 9 ], and 67% in Malaysia [ 4 ]. Whereas the proportion of perception towards tele-pharmacy was 87% in the University of Tennessee [ 8 ], 70.6% in Jordan [ 10 ], 61% in Malaysia [ 4 ], and 40% in Pakistan [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the proportion of perception towards tele-pharmacy was 87% in the University of Tennessee [ 8 ], 70.6% in Jordan [ 10 ], 61% in Malaysia [ 4 ], and 40% in Pakistan [ 11 ]. Furthermore, evidences revealed that technological variables and socio-demographic characteristics were discovered to be the determinant factors associated to students' knowledge of and perceptions of the tele-pharmacy system [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the COVID-19 pandemic in a city of Vietnam, Dat et al reported that 87% of the pharmacists used telepharmacy in their pharmacy practice. They also claimed that giving medical information and remote medicine guidance had become a compulsion in the context of the COVID-19 outbreak [ 19 ]. Even though the pharmacists might not have enough knowledge about telepharmacy now, but due to this need to practice and continuous exposure, they might be forced to increase their knowledge on telepharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Dat et al reported that about 87% of pharmacists have used telepharmacy in their pharmacy practice in response to the COVID-19 pandemic in Ho Chi Minh City, Vietnam. They also reported that the provision of medical information and remote medication counseling was an urgent need in the context of limited travel because of the COVID-19 pandemic [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Omran et al the main barriers to telepharmacy practice included a lack of professional training, ethical concerns, and a formal practice framework [ 19 ]. Dat et al reported that about 87.2% of the pharmacists in their study were ready to use telepharmacy [ 22 ]. Pharmacy colleges should incorporate telepharmacy practice models into their curricula in order to better prepare future pharmacists to provide telepharmacy services.…”
Section: Discussionmentioning
confidence: 99%